As an Ecodystopia, Water Crisis in “Susuz Çağın Çocukları” - Bulut, Funda; Öztürk, Elif Nur (Prensip Publishing, 2024)
While Ecodystopia tries to reveal how ecological destruction will affect the world and humans, it brings scientific facts - which are difficult to understand at first glance- about environmental problems into fiction in different ways and on the other hand, it draws attention on how the ecological crises will change people's daily lives and habits. In this research, it is aimed to reveal the reflections of climate change and water crisis in literature through the work called Susuz Çağın Çocukları, which is an ecodystopian fiction. In the research, whose theoretical framework is based on ecodystopia definitions, the data obtained from the work are divided into certain headings/themes through content analysis and interpreted with a focus on the water crisis. The work titled Susuz Çağın Çocukları, which is based on how life in the world will be shaped when no precautions are taken against the water crisis, tells the struggle for survival of people who have to establish a new civilization due to water scarcity. The author, who draws attention to the thought provoking consequences of climate disasters via children struggling to survive in the Dry Age Civilization, tries to reveal the possible consequences of the water crisis in the context of the foundations of dystopian fiction. Selda Yaşar who tries to bring ecological sensitivity to the reader, reminds the importance of values such as "sacrifice, determination, optimism, diligence and justice" to the child/young reader by constructing a solution-oriented optimistic world instead of creating a pessimistic perception of the future.
Keywords: 13. Climate action; 6. Clean water